Quantitative analysis of amino acid excretion by Methanothermobacter marburgensis under N2-fixing conditions - Barbara Reischl; Benjamin Schupp; Hayk Palabikyan; Barbara Steger-Mähnert; Christian Fink; Simon K.-M. R. Rittmann (Scientific Reports)
Abstract Methanogenic archaea (methanogens) possess fascinating metabolic characteristics, such as the ability to fix molecular nitrogen (N2). Methanogens are of biotechnological importance due to the ability to produce methane (CH4) from molecular hydrogen (H2) and carbon dioxide (CO2) and to excrete proteinogenic amino acids. This study focuses on analyzing the link between biological methanogenesis and amino acid excretion under N2-fixing conditions. Among five hydrogenotrophic, autotrophic methanogens, Methanothermobacter marburgensis was prioritized and further cultivated in closed batch cultivation mode under N2-fixing conditions. M. marburgensis was grown on chemically defined minimal medium with different concentrations of ammonium in a H2/CO2/N2 atmosphere. This enabled the quantification of ammonia uptake, N2-fixation, amino acid excretion and the conversion of H2/CO2 to CH4. To quantify N2-fixation rates in a mass balance setting a novel method has been established. The method utilizes the pressure drop below a certain threshold pressure in closed batch cultivation mode – the threshold pressure for N 2 -fixation (THpN2fix). Using the THpN2fix method, volumetric N2-fixation rates of M. marburgensis as high as 0.91 mmol L−1 h−1 were determined. Excretion of amino acids was found with highest detected values of glutamic acid, alanine, glycine and asparagine. The highest total amino acid excretion of 7.5 µmol L−1 h−1 was detected with H2/CO2/N2 at an ammonium concentration of 40 mmol L−1. This study sheds light on the link between methanogenesis, biological N2-fixation, and proteinogenic amino acid excretion. The concomitant production of amino acids and CH4 could become of biotechnological relevance in an integrated approach coupling biomethanation and N2-fixation in a biorefinery concept.